Microbial C, N and P in soils of Mediterranean oak forests: influence of season, canopy cover and soil depth - Aponte, Cristina; Marañón, Teodoro; García, Luis V. (Biogeochemistry, 2010)
In Mediterranean ecosystems the effect of aboveground and belowground environmental factors on soil microbial biomass and nutrient immobilization-release cycles may be conditioned by the distinctive seasonal pattern of the Mediterraneantype climates. We studied the effects of season, canopy cover and soil depth on microbial C, N and P in soils of two Mediterranean forests using the fumigation-extraction procedure. Average microbial values recorded were 820 lg C g -1 , 115 lg N g -1 and 19 lg P g -1 , which accounted for 2.7, 4.7 and 8.8% of the total pools in the surface soil, respectively. Microbial N and P pools were about 10 times higher than the inorganic N and P fractions available for plants. Microbial C values differed between forest sites but in each site they were similar across seasons. Both microbial and inorganic N and P showed maximum values in spring and minimum values in summer, which were positively correlated with soil moisture. Signiﬁcant differences in soil microbial properties among canopy cover types were observed in the surface soil but only under favourable environmental conditions (spring) and not during summer. Soil depth affected microbial contents which decreased twofold from surface to subsurface soil. Microbial nutrient ratios (C/N, C/P and N/P) varied with seasons and soil depth. Soil moisture regime, which was intimately related to seasonality, emerged as a potential key factor for microbial biomass growth in the studied forests. Our research shows that under a Mediterranean-type climate the interaction among season, vegetation type and structure and soil properties affect microbial nutrient immobilization and thus could inﬂuence the biogeochemical cycles of C, N and P in Mediterranean forest ecosystems.
Keywords: á; dynamics á; Microbial biomass; microbial biomass á nitrogen; nitrogen; Nutrient immobilization; nutrient immobilization á phosphorus; phosphorus; Plant; Plant–soil interactions; seasonal dynamics; soil interactions á seasonal; vegetation cover